+0

# the recursive rule

+5
393
1

the recursive rule of sequence is f(n)=f(n-1)-6 if the first term is 20 what is the fourth term of the sequance

Guest Dec 16, 2015

#1
+18827
+15

the recursive rule of sequence is f(n)=f(n-1)-6 if the first term is 20 what is the fourth term of the sequance

$$\begin{array}{rcll} f(n) &=& f(n-1) - 6 \\\\ f(2) &=& f(1) - 6 \qquad f(1) = 20\\ f(2) &=& 20 - 6 \\ f(2) &=& 14 \\\\ f(3) &=& f(2) - 6 \qquad f(2) = 14\\ f(3) &=& 14 - 6 \\ f(3) &=& 8 \\\\ f(4) &=& f(3) - 6 \qquad f(3) = 8\\ f(4) &=& 8 - 6 \\ \mathbf{f(4)} &\mathbf{=}& \mathbf{2} \end{array}$$

heureka  Dec 16, 2015
Sort:

#1
+18827
+15

the recursive rule of sequence is f(n)=f(n-1)-6 if the first term is 20 what is the fourth term of the sequance

$$\begin{array}{rcll} f(n) &=& f(n-1) - 6 \\\\ f(2) &=& f(1) - 6 \qquad f(1) = 20\\ f(2) &=& 20 - 6 \\ f(2) &=& 14 \\\\ f(3) &=& f(2) - 6 \qquad f(2) = 14\\ f(3) &=& 14 - 6 \\ f(3) &=& 8 \\\\ f(4) &=& f(3) - 6 \qquad f(3) = 8\\ f(4) &=& 8 - 6 \\ \mathbf{f(4)} &\mathbf{=}& \mathbf{2} \end{array}$$

heureka  Dec 16, 2015

### 8 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details